Psychosocial aspects, body composition and hemodynamics parameters in Scouts. - Venâncio, Patrícia Espíndola Mota; Fernandes, Mário Henrique; Soares, Viviane; Oliveira-Silva, Iransé; Pires-Oliveira, Deise Aparecida de Almeida; Lima, William Alves; Ribeiro, Henrique Lima; Tolentino, Grassyara Pinho (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: In order for the activities carried out by the boy scouts to achieve the objectives foreseen in their planning, it is important to have concrete data on the physical situation of children and adolescents, such as blood pressure, knowledge of how children are related to their degree of stress, anxiety and depression. Objectives: To identify blood pressure, Body mass index (BMI), and scores of stress, anxiety and depression in boy scouts from 7 to 17 years of age from the Bernardo Sayão Scout Group of the city of Anápolis in Goiás. Material and method: Adolescents from 7 to 17 years of age of both genders. BMI data were collected and a stress, anxiety and depression questionnaire was applied and blood pressure was measured. The normality of the data was verified with the Shapiro-Wilk test. The difference between the three groups was verified by the Dunusk’s post-hoc Kruskall-Wallis test. The categorical variables were analyzed by the Chi-square and the Spearman correlation coefficient verified the relationship between age and the variables Systolic Blood Pressure (SBP), Dyastolic Blood Pressure (DBP), BMI, anxiety, depression and stress. Results: The SBP of the participants in the “little wolf” category was inferior when compared to the scouts (p <0.001) and senior (p = 0.004), and the same happened with the PAD (little wolf x scout, p = 0.03 and little wolf x senior, P = 0.005). An association was found between BMI and sections. Most of the juniors, scouts and seniors were underweight. Among scouts children and adolescents there was a significant association with stress. In the category of the “little wolf” was found 53.60% of the children with very intense stress. The correlation between the variables SBP, DBP, BMI, anxiety, depression and stress with the age of children and adolescents. Age correlated negatively with anxiety, depression, and stress. Thus, as children are younger increases the degree of anxiety, depression and stress. Conclusion: The little wolf category had better BP results than the other categories, but they had higher levels of stress, depression and greater anxiety.